Telisik Determinan Kinerja Sistem Informasi Akuntansi : Studi Pada Perusahaan Perhotelan di Semarang - Ardiani Ika Sulistyawati; Aprih Santoso; Septi Ratnasari (ITB AAS INDONESIA, 2021)
The purpose of this study is to provide empirical evidence and analyze the influence of user friendliness, top management support, system formalization, education and training and company size on the performance of accounting information systems. The population in this study are hospitality employees whose work uses accounting information systems. The number of samples used was 103 respondents using purposive sampling technique. This research instrument was in the form of a questionnaire with Likert scale measurement. The analysis technique used in this study is multiple linear regression analysis. From the results of this study indicate the influence of user involvement, the formalization of the system has no effect on the accounting information system and top management support, education and training, company size influences the accounting information system Keywords: accounting information system